Low temperature formation of Mg2FeH6 by hydrogenation of ball-milled nano-crystalline powder mixture of Mg and Fe - Fadonougbo, Julien O.; Jung, Jee-Yun; Suh, Jin-Yoo; Lee, Young-Su; Shim, Jae-Hyeok; Cho, Young Whan (Elsevier BV, 2017)
Low temperature formation of Mg2FeH6 is demonstrated by hydrogenation of Mg-Fe elemental powder mixture at a temperature as low as 350 degrees C which is lower than the conventional process temperature, 500 degrees C. To enable the low temperature synthesis, the powder mixture of Mg and Fe has been prepared by high energy ball milling using different process control agents (PCAs). A systematic study on the ball milling and hydrogenation conditions has been carried out to maximize the yield of the ternary line compound. The hydrogenation conditions together with the particle size of the starting materials turn out to play a significant role in the hydrogenation kinetics of the system. An optimized condition has demonstrated a significant hydrogenation as well as a robust cycling ability at low temperature which suggests the strong potential of the process for practical applications. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: STORAGE PROPERTIES; DECOMPOSITION; HYDRIDES; HEAT